Implementation of Virtual Mobility and Internationalization at Home in Albania's Higher Education: A Catalogue of Recommendations for Action - Gotje Frieda Rubarth; Lisa Aschenbrenner; Maroua Salhi; Mattis Altmann (International School for Social and Business Studies, 2023)
Purpose: Despite progressing research in the field of Virtual Mobility and Internationalization at Home, recent theories and technologies are challenging to implement for Higher Education Institutes (HEIs). The present paper focuses particularly on Albania, where the current education system has not been able to sufficiently incorporate Virtual Mobility and Internationalization in higher education programs. Study design/methodology/approach: This paper analyses the prevalent situation within Albania's higher education system regarding Virtual Mobility and Internationalization at Home activities. The underlying data has been collected in qualitative semi-structured interviews, conducted with teaching staff and students from Albanian universities who are experienced with Virtual Mobility modules. It was evaluated through a mixed approach of qualitative content analysis by Mayring (2014) using inductive and deductive category formation. Findings: The results show the benefits that an increasing integration of Virtual Mobility activities in the education system could facilitate for students and teachers in Albania's HEIs. Nevertheless, it became clear that in order to implement a higher degree of Virtual Mobility at university level, it is necessary to overcome the legal obstacles set by the Ministry of Education as well as structural obstacles within the HEIs. Originality/value: Due the actual lack of development, concepts, infrastructures, and legal foundations, the implementation of Virtual Mobility as an affordable instrument to foster the international experience of Albanian students is of high importance. This could raise the quality of academic education and tackle capacity gaps in the education system of Albania towards the grade of international experiences of students.